Synthesis of Polysulfone Based Amphiphilic Graft Copolymers by a ‘Grafting to’ Approach - Mustafa Ciftci (Journal of the Turkish Chemical Society, Section A: Chemistry, 2019)
Synthesis of amphiphilic polysulfone graft copolymers by ‘‘Click’’ chemistry is described. First, a commercial PSU was chloromethylated to give chloro-funtional PSU (PSU-Cl). Subsequently, chloride groups were converted into azide moieties by nucleophilic substitution. Hydrophilic poly(N,N-dimethylacrylamide) (PDMA) side chains were then attached via a “grafting to” approach by using copper-catalyzed azide–alkyne cycloaddition (CuAAC). Precursor polymer and the final amphiphilic copolymers were characterized by 1H NMR, FT-IR, GPC and contact angle measurements.